Barriers to migrant worker unionization: Examining the impact of structural and subjective barriers to migrant worker unionization in the UK. (27th August 2018) - Theodoropoulos, Panos
Abstract : Despite being disproportionately concentrated in the most precarious jobs of the UK labor market, migrant workers are disproportionately absent from unions. This study aims to examine the structural and subjective impediments to migrant worker unionization. Not only to address subjectivities but also to counter the exclusion of migrant voices from the relevant literature, a qualitative approach employing interviews and an auto‐ethnography was chosen. It is argued that, alongside a variety of subjective and structural factors, the almost total absence of trade unions from many migrants' lives is a significant contributor to their lack of participation. The study concludes with some recommendations toward improving union outreach to migrant communities, arguing that a substantial part of trade unions' "traditional, " hierarchical, class‐centered remit must be overturned and replaced by intersectional and nonhierarchical organizing methods in order for them to be able to organize, work with, and empower migrant workers.